Deficient arginase II expression without alteration in arginase I expression attenuated experimental autoimmune encephalomyelitis in mice. Issue 1 (16th April 2018) - Choudry, Mariam; Tang, Xiaolei; Santorian, Tiffany; Wasnik, Samiksha; Xiao, Jidong; Xing, Weirong; Lau, Kin‐Hing William; Mohan, Subburaman; Baylink, David J.; Qin, Xuezhong
Summary: In the past there have been a multitude of studies that ardently support the role of arginase II (Arg II) in vascular and endothelial disorders; however, the regulation and function of Arg II in autoimmune diseases has thus far remained unclear. Here we report that a global Arg II null mutation in mice suppressed experimental autoimmune encephalomyelitis (EAE), an animal model of multiple sclerosis. During EAE, both Arg I and Arg II were induced in spinal cords, but only Arg II was induced in spleens and splenic dendritic cells (DCs). DC activation by lipopolysaccharide (LPS), CD40L or TLR8 agonist significantly enhanced Arg II expression without affecting Arg I expression. Conversely, DC differentiating cytokines [IL‐4 and granulocyte macrophage‐colony‐stimulating factor (GM‐CSF)] yielded opposite effects. In addition, Arg I and Arg II were regulated differentially during Th1 and Th17 cell polarization. Arg II deficiency in mice delayed EAE onset, ameliorated clinical symptoms and reduced myelin loss, accompanied by a remarkable reduction in the EAE‐induced spinal cord expression of Th17 cell markers (IL‐17 and ROR γ t). The abundance of Th17 cells and IL‐23 + cells in relevant draining lymph nodes was significantly reduced in Arg II knockout mice. In activated DCs, Arg II deficiency significantly suppressed the expression of Th17‐differentiating cytokines IL‐23 and IL‐6. Interestingly, Arg II deficiency did not lead to any compensatory increase in Arg I expression in vivo and in vitro . In conclusion, Arg II was identified as a factor promoting EAE likely via an Arg I‐independent mechanism. Arg II may promote EAE by enhancing DC production of Th17‐differentiating cytokines. Specific inhibition of Arg II could be a potential therapy for multiple sclerosis. Abstract : We found that arginase II (Arg II) deficiency in mice significantly protected against experimental autoimmune encephalomyelitis, an animal model of multiple sclerosis (MS). This protective effect is likely due to the compromised ability of the dendritic cells to induce Th17 cell differentiation. Arg II could be a potential drug target for development of therapy to treat MS.